THE RELATIONSHIP BETWEEN PREGNANT WOMEN’S PERCEPTION OF THE INTEGRATED ANC PROGRAM WITH PREGNANT WOMEN’S BEHAVIOR IN THE INTEGRATED ANC PROGRAM - Urip Tugiyarti Tugiyarti; Santoso Santoso Santoso; Muhammad Akhyar Akhyar; Sapja Anantanyu Anantanyu (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Relationship between Pregnant Women’s Perception of the Integrated ANC Program with Pregnant Women’s Behavior in the Integrated ANC Program Urip Tugiyarti(1), Santoso (2), Muhammad Akhyar(3), Sapja Anantanyu(4) 1) Study Program of Community Development/Empowerment Counseling in Health Promotion Interest, Universitas Sebelas Maret Surakarta 2)Faculty of Medicine, Universitas Sebelas Maret Surakarta 3) Faculty of Education, Universitas Sebelas Maret Surakarta 4) Development Counseling Study Program, Universitas Sebelas Maret Surakarta ABSTRACT Background: Maternal Mortality Ratio (MMR) is very high in the world; recorded 800 women die every day due to complications of pregnancy and childbirth. The causes of maternal mortality in Indonesia are very diverse, both medical and non-medical. For this reason, efforts to accelerate the reduction of MMR and accelerate the SDGs achievement must be carried out comprehensively by involving cross-programs in the Health Office, across sectors, DPRD in local government, professional, religious/community organizations, private sector, NGOs and donor institutions. This is relevant as a reference, because maternal health conditions, especially pregnant women, in Indonesia are still far from expectations. Ensuring maternal health efforts is not limited to curative treatment, but must be balanced with preventive efforts. Preventive efforts are very important, because health status cannot be obtained instantly. The preventive effort aims to prevent the occurrence of maternal deaths and fulfill the rights of every pregnant woman to obtain quality health services so that she is able to undergo a healthy pregnancy, deliver safely and give birth to a healthy and quality baby, and pregnant women must understand and carry out integrated antenatal care (ANC). The purpose of this study was to determine the relationship between perceptions of pregnant women about the integrated ANC program with the behavior of pregnant women in the integrated ANC program. Subject and Method: This study uses a quantitative research method with a cross sectional approach carried out in Bantul Regency. 175 respondents were selected using the cluster proportional random sampling technique. The criteria of respondents are pregnant women with more than 12 weeks gestational age in second and third Trimester. The instruments of data collection used were questionnaires. Data were analyzed with path analysis method and SEM to test the correctness of the structural models available on the lisrel program. Research Result: The results of the analysis show that there is a relationship between the perception of pregnant women about the integrated ANC program with the mother behavior in the integrated ANC program (0.42, t value = 8.70). Conclusion: There is a positive and significant relationship between the perceptions of pregnant women about the integrated ANC program with the mother behavior in the integrated ANC program. Keywords: pregnant women, perception, pregnant women behavior, integrated ANC program.